The Influence of Physical Education on the Character Development of Students at Mis Al Hafza Islamic Global School - Hafza, Abyena; Fadilah Siregar, Amelia Rika; Amalia Daulay, Siti; Suyono, Suyono (Jurnal Media Informatika, 2024)
Character and behavior development should start from an early age, in this case education. Education is an important thing that is taught to the community and at an early age a person receives various kinds of information that will affect their growth and development. Physical Education is one of the important sectors in the development of character and behavior and will affect the formation of children's character from an early age which is an inseparable part of education in general which affects the potential of students in terms of cognitive, affective, and psychomotor through physical activity. The behavior obtained through school programs is not only limited to the scope of factors from outside the school also affects the development of character and behavior of children, especially early childhood and elementary school. Early childhood is the most important and fundamental initial period in the span of growth and development of human life experiencing different periods of motor and skill development.